2023
DOI: 10.1111/ajae.12375
|View full text |Cite
|
Sign up to set email alerts
|

Optimal index insurance and basis risk decomposition: an application to Kenya

Abstract: Index insurance is a promising tool to reduce the risk faced by farmers, but high basis risk, which arises from imperfect correlation between the index and individual farm yields, has limited its adoption to date. Improving adoption will require reducing one or both of the two fundamental sources of basis risk: the intrinsic heterogeneity within an insurance zone (zonal risk), and the lack of predictive accuracy of the index (design risk). Previous work has focused mostly on design risk, conflating the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This explains the significance of September The method and model to set up threshold and premium is not covered in this paper, because it requires knowledge of agriculture and actuarial science [10]. Current studies have shown satellite data are more accurate and preferred for risk management, but the precipitation data in the United State climate data may not come from satellites [11,12]. Other data such as the type of sweet potato grown by farmers can also be incorporated into the yield model, as the model would not depend only on precipitation [13].…”
Section: Discussionmentioning
confidence: 99%
“…This explains the significance of September The method and model to set up threshold and premium is not covered in this paper, because it requires knowledge of agriculture and actuarial science [10]. Current studies have shown satellite data are more accurate and preferred for risk management, but the precipitation data in the United State climate data may not come from satellites [11,12]. Other data such as the type of sweet potato grown by farmers can also be incorporated into the yield model, as the model would not depend only on precipitation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Second, this paper provides new perspectives on farmers' apparently low demand for area insurance plans in the United States. The existing literature generally compares AYP with YP in effects on yield variance (Barnett et al, 2005; Miranda, 1991; Stigler & Lobell, 2021) or certainty equivalent revenues (Awondo & Datta, 2018; Deng et al, 2007). These methods depend on assumptions about the yield distribution or the utility function and underestimate the effect of basis risk on farmers' AYP choices.…”
Section: Introductionmentioning
confidence: 99%